Energy Security in Ecuador: An Analysis Considering the Interrelationships of the WEF Nexus - Carlos Francisco Terneus-Páez; Oswaldo Viteri-Salazar (Energies, 2023)
The objective of this research was to analyze energy security in Ecuador, which is interconnected with water and food security. As a methodology, 21 indicators grouped into the following dimensions were analyzed: availability, infrastructure, energy prices, efficiency, social impact, environment and governance. For each indicator, a cross-sectional analysis was carried out with the countries of Colombia, Peru and Bolivia, along with a longitudinal analysis from 2011 to 2021. The main contribution of this study is the characterization of the Ecuadorian energy system as available, accessible, affordable and renewable in an electrical matrix but inefficient and heavily dependent on fiscal resources. The factors that may affect Ecuador’s energy security were determined to be the risk of a reduction in income due to it becoming a net importer of energy, climate change, socio-environmental conflicts, poor diversification, energy subsidies and weak governance. A policy is proposed aimed at decoupling development from fossil fuels, with a systemic vision considering the complexity of interactions with other economic sectors, such as water and food, among others.